ANALISIS PERLAKUAN AKUNTANSI ASET TETAP PADA BADAN KEPEGAWAIAN DAN DIKLAT (BKD) KOTA MANADO - Masipuang, Yefta; Ilat, Ventje; Pinatik, Sherly (Universitas Sam Ratulangi, 2015)
This study aimed to analyze the accounting treatment for fixed assets in Manado what BKD in accordance with Regulation 71 Year 2010 Statement of Government Accounting Standards (PSAP) No. 07 on fixed assets. The method used is descriptive analysis method with a way of understanding reality and compare it with the theory that the researchers studied so it can be concluded. In the research entity accounting treatment of fixed assets has been good. In practice, in the way of acquisition of fixed assets of the entity making a purchase in cash, the entity has not shrunk its fixed assets where it is not in accordance with the Governmental Accounting Standards applicable, the entities stop fixed assets that are not used by way of eliminating it from the balance sheet and transferred to the post of other fixed assets , as well as in the presentation and disclosure, the entity has revealed the fixed assets in accordance with accounting standards applicable rule.